Messianic Ethics: Jesus' Kingdom-of-God Proclamation and the Appropriate Response - Wiebe, Ben (My University, 1988)
How are the eschatology and ethics related in Jesus' proclamation of the kingdom of God and in the response to it that he hoped to win from Israel? How is the ethical dimension of the intended response formed or informed by the kingdom of God? In the history of scholarship the search for the coherence between Jesus' eschatological message and the response to it that he intended to win inevitably raised the question of the relation between "kingdom" and ethics. Albrecht Ritschl's influential view affirmed the closest bond between them: the kingdom of God is to be realized in and by human ethical action. This way of stating the relationship of shattered by the compact work of Johannes Weiss on Jesus' proclamation of the kingdom of God. If it is not possible simply to follow Weiss (or Schweitzer, who followed up on and refined the position of Weiss). It is also impossible to bypass him. Therefore in chapter one I outline the position of Ritschl and the response of Weiss' influential exposition of the kingdom of God. This is followed by an attempt to examine the relation between eschatology and ethics in the work of representative scholars from the past one hundred years. This interpretation of the kingdom of God in Jesus' proclamation depends significantly on what is presupposed about the resourced from which he drew in making his proclamation and carrying out his mission. There I survey Jewish writings with the ultimate aim of determining what was clearly important for Jesus. Furthermore, these sources give evidence of a relation between (eschatological) promise and appropriate ethical response. In the interpretation of Jesus' Kingdom-of-God proclamating attention has been directed either to eschatology or to ethics at one time the primary focus was on the human ethical response (e.g. Harnack), at another time on the activity of God (e.g. Jogannes Weiss). If it is true that eschatology and ethics exist in religion in the proclamation and teaching of Jesus, it follows that they may only be properly or clearly understood in a study that examines them in their relationships. This calls for a critical correlation of Jesus' eschatological message and his ethical teaching. Jesus' eschatological proclamation and the intended ethical response become concrete only with a recovery of the purposes of Jesus bearing on the whole people, Israel, to whom he came (chapter three). In chapter four I examine Jesus' kingdom-of-God proclamation defined more sharply and fully in the context of his mission and death as this was expressed in the esoteric teaching of his disciples. And in this teaching the connection between Jesus' own destiny and his ethics of discipleship is emphasized. A reasonably accurate comprehension of the ethics of Jesus depends on a reasonably accurate recovery of the whole historical figure that he was. The present study accordingly pays attention to the historical bases for the understanding of Jesus' ethical teachings whether in the public forum-or in the more intimate circles of his discipleship.
Keywords: Biblical Studies; Biblical Studies